2017
DOI: 10.1017/s1366728917000566
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences predict ERP signatures of second language learning of novel grammatical rules

Abstract: We investigated the extent to which second-language (L2) learning is influenced by the similarity of grammatical features in one's first language (L1). We used event-related potentials to identify neural signatures of a novel grammatical rule – grammatical gender – in L1 English speakers. Of interest was whether individual differences in L2 proficiency and age of acquisition (AoA) influenced these effects. L2 and native speakers of French read French sentences that were grammatically correct, or contained eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…Previous ERP research on L2 processing in late learners has suggested that there may be hard constraints for morpho-syntactic processing, especially for grammatical structures that are not shared between the L1 and the L2 (e.g., Nichols & Joanisse, 2017; Sabourin & Stowe, 2008; Sabourin, Stowe & de Haan, 2006). However, despite the difficulty of acquiring L2 grammatical structures, a number of recent ERP studies have revealed that at least a subset of late L2 speakers with extensive immersion experience (e.g., Dowens et al, 2010) or with high proficiency levels (e.g., Rossi et al, 2014; Foucart & Frenck-Mestre, 2012; Tokowicz & MacWhinney, 2005) show a similar neural signature to native speakers (for evidence using an artificial language, see Morgan-Short, Sanz, Steinhauer & Ullman, 2010), even for unique grammatical structures of the L2 that are not encoded in the L1 (Foucart & Frenck-Mestre, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous ERP research on L2 processing in late learners has suggested that there may be hard constraints for morpho-syntactic processing, especially for grammatical structures that are not shared between the L1 and the L2 (e.g., Nichols & Joanisse, 2017; Sabourin & Stowe, 2008; Sabourin, Stowe & de Haan, 2006). However, despite the difficulty of acquiring L2 grammatical structures, a number of recent ERP studies have revealed that at least a subset of late L2 speakers with extensive immersion experience (e.g., Dowens et al, 2010) or with high proficiency levels (e.g., Rossi et al, 2014; Foucart & Frenck-Mestre, 2012; Tokowicz & MacWhinney, 2005) show a similar neural signature to native speakers (for evidence using an artificial language, see Morgan-Short, Sanz, Steinhauer & Ullman, 2010), even for unique grammatical structures of the L2 that are not encoded in the L1 (Foucart & Frenck-Mestre, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Differential signatures of L2 processing have also been driven by an interaction of linguistic factors (i.e., similarity across grammatical structures between the L1 and the L2), and speakers’ factors such as age of acquisition and proficiency. For instance, Nichols and Joanisse (2017) propose a graded model for L2 processing according to which proficiency and age of acquisition might play partly independent roles in shaping the ERP signatures to different types of violations. For example, proficiency levels seem to be important for early stage markers of grammatical processing such as the Left Anterior Negativity in response to grammatical violations for syntactic structures that overlap between the two languages, while age of acquisition seems to play an independent role in shaping the neural response for grammatical structures that are not shared between the two languages.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, regions involved in executive and attentional control (e.g., dorsolateral prefrontal cortex and insula) are likely to show less differentiation in how each language is represented as the function of these regions should not differ qualitatively from one language to another. Individual differences in language ability and experience also play an important role in bilingual language processing (Newman, Tremblay, Nichols, Neville, & Ullman, 2012; Nichols & Joanisse, 2016, 2017) and may affect the integration of the neural representation of each language. Previous research indicates that low proficiency speakers and late L2 learners have greater separation of their two languages' conceptual knowledge (Van Hell & Tanner, 2012), and this separation may also be reflected in the neural representation of words and concepts within co‐activated brain areas.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, regions involved in executive and attentional control (e.g., dorsolateral prefrontal cortex and insula) are likely to show less differentiation in how each language is represented as the function of these regions should not differ qualitatively from one language to another. Individual differences in language ability and experience also play an important role in bilingual language processing 11,15,16 , and may affect the integration of the neural representation of each language.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, regions involved in executive and attentional control (e.g., dorsolateral prefrontal cortex and insula) are likely to show less differentiation in how each language is represented as the function of these regions should not differ qualitatively from one language to another. Individual differences in language ability and experience also play an important role in bilingual language processing 11,15,16 , and may affect the integration of the neural representation of each language. Previous research indicates that low proficiency speakers and late L2 learners have greater separation of their two languages’ conceptual knowledge 17 , and this separation may also be reflected in the neural representation of words and concepts within co-activated brain areas.…”
Section: Introductionmentioning
confidence: 99%